1981
DOI: 10.17763/haer.51.2.287538161u398060
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Pedagogy of Experience

Abstract: David Thornton Moore develops a framework for analyzing the social organization of education in nonclassroom environments, presenting his observations of students in an experiential learning program over a three year period. He argues that the process of education must be understood as being shaped by certain nonpedagogical features of the broader social context within which it occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Just adding a service project or placement to a course does not guarantee that students will reflect on ways that the experience relates to their academic study. Moore (1981Moore ( , 1999 found that students in work placement in communities were rarely asked to explicitly link their experience with their academic study or to think about its wider implications. Their community activities were often routine and repetitive and contributed little to a broader understanding of the work or the workplace.…”
Section: Planning For Effective Reflection: the Reflection Mapmentioning
confidence: 99%
“…Just adding a service project or placement to a course does not guarantee that students will reflect on ways that the experience relates to their academic study. Moore (1981Moore ( , 1999 found that students in work placement in communities were rarely asked to explicitly link their experience with their academic study or to think about its wider implications. Their community activities were often routine and repetitive and contributed little to a broader understanding of the work or the workplace.…”
Section: Planning For Effective Reflection: the Reflection Mapmentioning
confidence: 99%
“…A number of other researchers have developed related ways of systematizing ethnographic or qualitative data Green & Wallat, 1979;Mehan, 1979;Mehan & Riel, in press;Moore, 1981). Systematic analyses of functional patterns in interactional data also appear in other scholarly traditions, such as ethology (Grossmann, 1981), infant social interaction research (Als, Tronick, & Brazelton, 1979;Uzgiris & Fafouti-Milenkovic, 1985), and the hermeneutic tradition (Kreppner, Paulsen, & Schuetze, 1982).…”
Section: Ill Analysis Strategy For the Observationsmentioning
confidence: 99%
“…In a sense, these "social means" features constitute the pedagogy of work experience, because they represent the choices participants make in shaping the intern's access to situated knowledge (Moore 1981a). On the other hand, the features of the tasks themselves may be thought of as the naturally occurring curriculum of work, because they represent the knowledge to which the newcomer gains access (Moore 1982).…”
Section: The Approachmentioning
confidence: 99%
“…While we understood that high school interns are hardly representative of full-time workers, we wanted to find out how newcomers in work organizations learn. The framework we generated has been reported extensively elsewhere (Moore 1981a(Moore , 1981b. The following is a brief explanation of the approach and a comparative educational analysis of two very different work settings.…”
mentioning
confidence: 99%